Associated petroleum gas utilization in Tomsk Oblast:energy efficiency and tax advantages; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Vazim A. A. Andrey Aleksandrovich; Romanyuk V. B. Vera Borisovna; Ahmadeev K.; Matveenko I. A. Irina Alekseevna (Petroleum Engineering Economics. Mining Law, 2015)
Title screen